2017
DOI: 10.1186/s12936-017-1684-4
|View full text |Cite
|
Sign up to set email alerts
|

Severe Plasmodium vivax infection in Korea

Abstract: BackgroundAlthough severe malaria by Plasmodium vivax has been increasingly reported, there are marked variations in the type and rate of the complications by geographic area. This is possibly because of the presence of concurrent falciparum malaria or bacteraemia, and of differences in underlying immune status among the infected subjects. Furthermore, published studies on P. vivax in temperate regions are limited. The present study investigated severe vivax malaria in Korea, where only vivax malaria occurs. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 37 publications
4
31
0
1
Order By: Relevance
“…P. vivax is the main etiology for malaria in South Korea, mostly present along the demilitarized zone 1. Our patient’s initial presentation of fevers and myalgia is consistent with the clinical picture of malaria 2.…”
Section: Discussionsupporting
confidence: 78%
“…P. vivax is the main etiology for malaria in South Korea, mostly present along the demilitarized zone 1. Our patient’s initial presentation of fevers and myalgia is consistent with the clinical picture of malaria 2.…”
Section: Discussionsupporting
confidence: 78%
“…Plasmodium vivax is the most widely distributed human malaria parasite. To date, several clinical complications have been reported in P.vivax-infected patients such as severe thrombocytopenia, acute renal failure, acute respiratory distress syndrome as well as cerebral malaria [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, SI is often detected incidentally when abdominal computed tomography (CT) is performed to identify the cause(s) of fever. While several investigations have shown that various pathogens can cause SI [4][5][6][7][8], comprehensive studies investigating the association between SI and infection are limited. One retrospective study reported that 4 of 32 patients with SI had infections [3], whereas another identi ed infection as the causative factor in 11 of 89 patients with SI [9].…”
Section: Introductionmentioning
confidence: 99%